73.2k views
3 votes
Plz answer fast

Which of the following expressions demonstrates the distributive property?

3 + 4 + 5 = 4 + 3 + 5

-2(5 + 7) = -2(7 + 5)

3(-8 + 1) = 3(-8) + 3(1)

6[(7)(-2)] = [(6)(7)](-2)

User Gelisa
by
4.8k points

2 Answers

4 votes

Answer:

3(-8+1) = 3(-8)+3(1)

Explanation:

HOPETHISHOPES!!

User Epic Speedy
by
5.5k points
4 votes

Answer:

3(-8+1) = 3(-8)+3(1)

Explanation:

you multiply the value(s) in front of the parentheses to the values in them.

User Bdorry
by
5.6k points